Analytical quality by design (AQbD) based optimization of RP-UPLC method for determination of nivolumab and relatlimab in bulk and pharmaceutical dosage forms - Mohana Vamsi Nuli; Ramanjaneyulu Seemaladinne; Anil Kumar Tallam (SpringerOpen, 2024)
Abstract Background The Analytical Quality by Design (AQbD) methodology extends the application of Quality by Design (QbD) principles to the management of the analytical procedure life cycle, encompassing method creation, optimization, validation, and continuous improvement. AQbD assists in creating analytical procedures that are robust, reliable, precise, and cost-efficient. Opdualag™ is a combination of Nivolumab and Relatlimab, which are antibodies that block programmed death receptor-1 (PD-1) and lymphocyte-activation gene 3 (LAG-3) receptors, used to treat advanced melanoma. This work aims to develop and validate a reversed-phase ultra-performance liquid chromatography (RP-UPLC) method using AQbD principles to determine NLB and RTB in pharmaceutical products. Results A central composite design (CCD) comprising three factors arranged in five distinct levels was implemented via Design-expert® software to optimize the chromatographic conditions. A mathematical model was constructed and the effects of three independent factors namely flow rate (X1), percentage of methanol in the mobile phase (X2), and temperature (X3) on responses including retention time (Y1-2), resolution factor (Y3), theoretical plates (Y4-5), and tailing factor (Y6-7) were investigated. The software determined the optimal chromatographic conditions for the separation of NLB and RTB, which were as follows: 32.80% methanol in the mobile phase, 0.272 mL/min flow rate, 29.42 °C column temperature, and 260 nm UV detection. The retention time for NLB and RTB were 1.46 and 1.88 min, respectively. The method exhibited linearity across the concentration ranges of 4-24 µg/mL for RTB and 12-72 µg/mL for NLB. The limits of detection (LOD) and limit of quantification (LOQ) for NLB and RTB, respectively, were 0.89 µg/mL, 2.69 µg/mL and 0.15 µg/mL and 0.46 µg/mL. The percentage relative standard deviation (%RSD) of intraday and interday precision for NLB and RTB was below 2. The recovery percentages for NLB and RTB were determined to be 99.57-100.43% and 99.59-100.61%, respectively. Both drugs were found to be susceptible to oxidative and photolytic degradation in forced degradation studies. Conclusions Employing the AQbD-based methodology, a straightforward, fast, accurate, precise, specific, and stability-indicating RP-UPLC method has been established for the quantitative analysis of NLB and its RTB in pharmaceutical formulations.